The Use of the Ricosre Method in Biology Lessons on the Characteristics and Structure of Viruses in High School Students - Nur Rizkiyah (Peneliti.net, 2021)
Suitable learning is needed for students and teachers. However, not all teachers can apply appropriate learning for their students. A good method for students is a method that can improve student learning outcomes. The purpose of this study is to describe the use of the Ricosre method in Biology lessons for Darul Faizin High School students, Bogor, to find out whether the Ricosre method can improve Biology learning outcomes for Darul Faizin High School students, Bogor and to find out how much learning improvement will be achieved in Darul Faizin High School students, Bogor. This research was conducted in Biology Subjects, Material Characteristics and Structure of Viruses. The research sample used in this study were students of class X SMKS Napala Bogor. the type of experiment is one type of group pre-test and post-test (The One Group Pretest Posttest). Treatment using the Ricosre method (mean of 64.9864 ) compared to before using the media (mean of 61.6240 ), increased by 3.36240. In other words, the use of media has a significant effect on the 95% confidence level. The Ricosre method can improve student learning outcomes, on Virus material. Ricosre's learning process activates students into unique and interesting learning. Students can solve existing problems. The material is clear and complete, making it easier for students to learn material about Viruses. Teachers can use this method, with new creativity and innovation.